The Fractal Approach as a Method for Strategic Regulation of the Educational and Economic Ecosystem of a Digital University - Bobro Natalia; Бобро Н.; Bobró N. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. In the current conditions of digitalization, structural transformations of the global labor market, and increased requirements for the adaptability of educational systems, there is a need to revise traditional approaches to regulating the training processes within university education. The article is devoted to the substantiation of the fractal approach as an effective method of strategic management of the educational and economic ecosystem of a digital university. A scientific model is proposed that considers the recursive, self-similar, multilevel, and dynamic nature of the digital educational environment and allows for ensuring the adaptability of educational structures to the challenges of the digital economy. The methodological foundations for the transformation of university education in the digital age are revealed, in particular in terms of building integrated quality indicators based on normalized indicators and principal components. The necessity of using multidimensional data, indices, expert opinions, ratings, and time series to analyze and predict the efficiency of digital university subsystems is substantiated. Mathematical formalizations are proposed that allow for the evaluation of fractal structures of the educational system at different hierarchical levels and the derivation of generalized integral performance indicators. Particular attention is paid to the use of artificial intelligence technologies, precedent modeling, and knowledge-based approaches in management decision-making. The article proves that a digital university is not only an educational organization, but also a complex socio-technical fractal system capable of selforganization, self-development, and flexible functioning under conditions of uncertainty. It is noted that the fractal approach allows for aligning strategic development goals with tactical and operational management actions at different levels of management. The approaches to modeling the educational and economic ecosystem of a digital university proposed by the author open up new prospects for forecasting the development of intellectual capital, optimizing management processes, and ensuring the sustainability of the educational system in the digital environment.

A digitális korszak, a globális munkaerőpiac strukturális átalakulása és az oktatási rendszerekkel szembeni fokozott alkalmazkodási igények fényében felmerül a szükségesség, hogy felülvizsgáljuk a hagyományos megközelítéseket a munkaerőképzés szabályozásában az egyetemi oktatás keretében. A cikk a fraktális megközelítés tudományos megalapozottságát tárgyalja, mint hatékony módszert a digitális egyetem oktatási-gazdasági ökoszisztémájának stratégiai irányításában. A kutatás egy tudományos modellt javasol, amely figyelembe veszi a digitális oktatási környezet rekurzív, önhasonló, több szintű és dinamikus természetét, valamint lehetővé teszi az oktatási struktúrák alkalmazkodását a digitális gazdaság kihívásaihoz. Részletesen bemutatásra kerülnek a digitális korszakban zajló egyetemi oktatás átalakításának módszertani alapjai, különös figyelmet fordítva az integrált minőségmutatók kialakítására a normalizált mutatók és fő komponensek alapján. Indokolt a többdimenziós adatok, indexek, szakértői értékelések, rangsorok és időbeli sorozatok alkalmazása az oktatási rendszer digitális egyetemi alrendszereinek hatékonyságának elemzésére és előrejelzésére. A cikk matematikai formalizmusokat javasol, amelyek lehetővé teszik a fraktális struktúrák értékelését az oktatási rendszer különböző hierarchikus szintjein, valamint segítenek az integrált működési mutatók megfogalmazásában. Külön figyelmet kapnak a mesterséges intelligencia technológiák, a precedensmodellezés és a tudásalapú megközelítések alkalmazása a döntéshozatalban. A cikk arra a következtetésre jut, hogy a digitális egyetem nemcsak oktatási szervezet, hanem egy összetett szociális-technikai fraktális rendszer is, amely képes az önszerveződésre, az önfejlesztésre és a rugalmas működésre a bizonytalanság környezetében. Megállapítást nyert, hogy a fraktális megközelítés lehetővé teszi a fejlesztési stratégiai célok összehangolását a különböző szintű taktikai és operatív irányítási lépésekkel. A szerző által javasolt megközelítések az oktatási-gazdasági ökoszisztéma modellezésére a digitális egyetemen új perspektívákat nyitnak az intellektuális tőke fejlődésének előrejelzésében, az irányítási folyamatok optimalizálásában és az oktatási rendszer fenntarthatóságának biztosításában a digitális környezetben.

Резюме. У сучасних умовах цифровізації, структурних трансформацій глобального ринку праці та підвищених вимог до адаптивності освітніх систем постає необхідність перегляду традиційних підходів до регулювання процесів підготовки кадрів у межах університетської освіти. Стаття присвячена обґрунтуванню фрактального підходу як ефективного методу стратегічного управління освітньо-економічною екосистемою цифрового університету. Запропоновано наукову модель, яка враховує рекурсивну, самоподібну, багаторівневу й динамічну природу цифрового освітнього середовища та дозволяє забезпечити адаптивність освітніх структур до викликів цифрової економіки. Розкрито методологічні засади трансформації університетської освіти в умовах цифрової епохи, зокрема в частині побудови інтегральних індикаторів якості на основі нормалізованих показників та головних компонент. Обґрунтовано необхідність використання багатовимірних даних, індексів, експертних оцінок, рейтингів і часових рядів для аналізу й прогнозування ефективності підсистем цифрового університету. Запропоновано математичні формалізації, які дозволяють здійснювати оцінювання фрактальних структур освітньої системи на різних ієрархічних рівнях та виводити узагальнені інтегральні показники діяльності. Особливу увагу приділено використанню технологій штучного інтелекту, прецедентного моделювання та знаннєвоорієнтованих підходів у прийнятті управлінських рішень. У статті доведено, що цифровий університет є не лише освітньою організацією, а й складною соціотехнічною фрактальною системою, яка здатна до самоорганізації, саморозвитку та гнучкого функціонування в умовах невизначеності. Зазначено, що фрактальний підхід дозволяє узгоджувати стратегічні цілі розвитку з тактичними й оперативними управлінськими діями на різних рівнях управління. Запропоновані автором підходи до моделювання освітньоекономічної екосистеми цифрового університету відкривають нові перспективи для прогнозування розвитку інтелектуального капіталу, оптимізації управлінських процесів і забезпечення сталості освітньої системи в цифровому середовищі.
Фрактальний підхід як метод стратегічного регулювання освітньо-економічної екосистеми цифрового університету
Fraktál megközelítés, mint a digitális egyetem oktatási és gazdasági ökoszisztémájának stratégiai szabályozási módszere
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/9
Keywords: digital university; fractal model; strategic regulation; educational and economic ecosystem; intellectual capital; digitalization